Senior Entrepreneurship: The Unrevealed Driver for Social Innovation - Stypińska, Justyna; Franke, Annette; Myrczik, Janina (Frontiers in Sociology, 2019)
From a political and economic perspective, senior entrepreneurship seems to be the response to demographic consequences of the ageing workforce in Europe. Several policies and strategies by the EU and the OECD promote senior entrepreneurship by creating favorable environment and frameworks. This article examines the role of senior entrepreneurship as social innovation understood as response to unmet needs of population ageing in the area of economic activity. In this paper, we draw on qualitative interviews with 6 experts and 4 senior entrepreneurs (as part of larger research project) in Poland in addition to the analysis of reports and evaluations of incubator projects. Findings highlight the importance of other factors than financial sustainability of senior entrepreneurship: (1) social connectedness as means against social isolation, (2) personal self-confidence leading to social and psychological empowerment of the entrepreneurs, (3) skills, knowledge, and experience also strengthening their human capital in the job market. Economic sustainability of the businesses established is not the primary goal in these undertakings. The article suggests due to the three factors before mentioned that the notion of social innovation in senior entrepreneurship might best be understood as improving the well-being and quality of life of the entrepreneurs themselves. Senior entrepreneurship can be an adequate response to the challenges of the ageing population. However, due to the low rates of unemployment, the idea of becoming a senior entrepreneur appears little tempting.